Pelaksanaan Ekstrakurikuler Pencak Silat Tingkat SMA/SMK Di Kabupaten Purbalingga Tahun 2019 (Universitas Negeri Semarang, 2021)
The purpose of this research is to determine the implementation of pencak silat extracurricular activities for high school / vocational high school level in Purbalingga Regency in 2019. This research used a qualitative descriptive approach. The methods of data collection using observation, interviews and documentation. Research subjects are supervisors, coaches, and students. The results showed that, the implementation of pencak silat extracurricular activitaies at the SMA / SMK level in Purbalingga Regency have been running well and smoothly based on the training program, implementation time, achievements and implementation processes that have been implemented according to schedule. So that from the results of the research, it can be concluded that the implementation of pencak silat extracurricular for SMA / SMK in Purbalingga Regency in 2019 has been going according to purpose. Even though there are still some inhibiting factors, the extracurricular implementation is running smoothly.